Measurement e-commerce Services Quality: Applying Webqual 4.0 and Importance Performance Analysis - Sucipto Sucipto; Cahyani Budihartanti (ICSE (Institute of Computer Sciences and Engineering), 2020)
One of the increasing use of technology in the business sector is the growing number of online-based business applications. Business actors began to develop many businesses through e-commerce websites. Shopee is an application that is engaged in buying and selling online and can be accessed easily using a smartphone. With a total visit of nearly 2 billion in 2019, Shopee grossed US942 million. But the buyer satisfaction rate of online transactions is still low compared to conventional purchases, in addition to reducing satisfaction, plus the risk of fraud that can be detrimental. The purpose of this research is to know the perception of consumers to the quality of service and analyze the consumer satisfaction of the Shopee website. The instruments used in this research are questionnaires with sampling techniques incidental. In this research, the method used is Webqual method 4.0 and IPA. In the Webqual method consists of the usability aspects, information quality and interaction quality. In the IPA method is used to analyze the level of conformity and gaps based on the level of satisfaction and expectation of users. The result of the calculation of the IPA method can be described with IPA matrix consisting of four quadrants. From the results of the analysis of this research, the value of Gap (GAP) is the largest aspect of interaction quality with an average value of 3.20%.